Because Amelia smiled - Stein, David Ezra. (Somerville, Mass. : Candlewick Press, 2012)
A little girl's smile as she skips down the street in New York inspires a neighbor to send cookies to her grandson in Mexico, and the good will soon spreads around the world.
Horn Book
Publisher's Weekly
School Library Journal
Horn Book, September 2012
Kirkus Review, August 2012
Publisher's Weekly, July 2012
Keywords: Caring -- Juvenile fiction; Thoughtfulness -- Juvenile fiction; Caring -- Fiction; Thoughtfulness -- Fiction; Caring -- Fiction; Thoughtfulness -- Fiction; Picture books for children